Upaya Peningkatan Penjualan UMKM di Rumah Makan Wong Solo 77 Medan Perjuangan - Silalahi, Flora; Sulaiman, Fahmi (Cattleya Darmaya Fortuna, 2023)
Efforts to Improve and Marketing Strategy for UMKM on Ayam Penyet Balap Solo 17 Medan Perjuangan. Supervised by Fahmi Sulaiman. This study aims to find out what efforts should be made to improve the marketing strategy for the food stall business at Ayam Penyet Balapan solo 17 Medan Perjuangan. Sampling in this study was carried out using informant techniques, namely business owners who conceptually know and understand the ins and outs of the strategies used and how to market their products, incoming and outgoing finances, the quality of work of employees, both sales, shipping and cashier employees. The strategy that needs to be recommended to the Ayam Penyet Balapan Solo 17 Medan Restaurant is using existing opportunities and strengths, including maintaining an Islamic restaurant business culture consistently with the support of a predominantly Muslim community, optimizing the management system, making the restaurant's Islamic culture a feature. typical of Balapan Solo 17 restaurants, improve fast and excellent service, provide discounts or special prices for loyal customers, and carry out promotional activities optimally. And the obstacles faced in increasing its market share are the lack of facilities and infrastructure in the development of marketing/promotion and the Wong Solo restaurant is not a fast food restaurant so that consumers are usually disappointed if the service in serving food is served slowly. Keywords: Marketing strategy, and SWOT analysis.